Menjual Keberkahan: Persepsi Generasi Z Terhadap Komersialisasi Agama pada Produk Air Mineral dan Garam di DKI Jakarta - Muhammad Saddam Husaini; Corry Yohana; Bagus Kharismawan (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
The commercialization of religion has increasingly appeared in marketing activities, including mineral water and salt products claimed to contain blessings. The use of religious symbols and narratives in product promotions has generated diverse perceptions, particularly among Generation Z, who live in an era of rapid technological development and easy access to information. This study aims to examine the perceptions of Generation Z in Jakarta regarding the commercialization of religion through such products, identify the factors influencing these perceptions, and explore their implications for business ethics and religious values. A qualitative approach was employed using in-depth interviews with six Generation Z informants in Jakarta, selected purposively. Data were analyzed using ATLAS.ti through coding and network analysis, with validity ensured through source triangulation. The findings reveal that Generation Z holds diverse perceptions. Some informants perceive blessings as spiritual values providing inner peace and strengthening religious commitment, while others view such claims as psychological suggestion or marketing strategies exploiting religious symbols. Influencing factors include spiritual experiences, religiosity levels, religious leaders, social environment, and social media exposure. Generation Z tends to be critical of religious claims lacking clear justification. From a business ethics perspective, using religious symbols is considered acceptable if conducted transparently and honestly. These findings indicate that the commercialization of religion represents an intersection between spiritual needs, economic interests, and growing consumer critical awareness in the digital era.